ANALISIS FAKTOR-FAKTOR YANG MEMPENGARUHI RETURN SAHAM PADA PERUSAHAAN MANUFAKTUR YANG TERDAFTAR DI BURSA EFEK INDONESIA PERIODE 2010 - 2014 - Bakung, Yosua Sumekara Himba; Hariyanti, Widi; Suseno, Agus Endrianto (Fakultas Ekonomi - Universitas Setia Budi, 2019)
This research aims to examining factors that affect stock returns. The dependent variable used in this study is stock returns. Independent variables used in this study is Economic Value Added (EVA), Operating cash flow, Residual Income, Earnings, Operating Leverage, dan Market Value Added (MVA). The population in this research is manufacturing companies listed in Indonesia Stock Exchange 2010-2014. The sample in this study is 21 companies selected by using purposive sampling method. This study used multiple linear regression analysis as an analytical tool. The results showed that H1 Economic Value Added ( EVA ) had no significant effect on stock returns . H2 Operating Cash Flow is not a significant effect on stock returns . H4 Earnings significant effect on stock returns . H5 Operating Leverage no significant effect on stock returns . H6 Market Value Added ( MVA ) had no significant effect on stock returns.